Exact expressions for dielectric susceptibilities in the paraelectric phase of ferroelectric superlattices based on the ginzburg-landau theory - Chew, Khian Hooi; Ishibashi, Y.; Iwata, M.; Shin, F.G. (2008)
Exact expressions for the polarization profiles induced by an external electric field and the dielectric susceptibilities in the paraelectric phase were obtained for a one-dimensional ferroelectric superlattice on the basis of the Ginzburg-Landau theory. The superlattice is composed of a ferroelectric of thickness L1 and a paraelectric of thickness L2, which couple each other through the polarization at their interfaces. Our analytical results revealed that the profile of polarizations induced by the electric field in the paraelectric phase may be considered to approximately represent the soft mode.